The Challenges of Gender Mainstreaming in Community Development Projects in Developing Countries: A Case Study of Self-Help Groups in Rural India - Helga Yohana Simatupang (Jurnal PIR : Power in International Relations, 2022)
In many developing countries, women are commonly married young, quickly become mothers, and then burdened by domestic work and financial responsibilities. As a result of these conditions, we now live in a world where women are living in poverty and are subjected to injustices and discrimination. This paper aims to examine the critical roles of women and the importance of their involvement in decision-making processes, including the challenges, failures, and success stories in implementing gender-just development strategies in developing countries, specifically India. Since India has been the world's second-most-populous country, the majority of people live in rural areas and millions face extreme poverty. The country is now in a process of rapid economic development, but it faces complex and enduring internal problems, such as those around the caste system. The gap between rich and poor in India is vast. This research uses a qualitative method with the help of a literature review that supports adequate analysis and discussion of the material in this research. In India, where a patriarchal system is deeply entrenched,women have long been denied the legal right to own land. Over the years, several strategies have been created to empower women. One of them is starting Self-Help Groups (SHGs) which are created by governmental organizations that generally have broad anti-poverty agendas. The goal of SHGs is to bridge the gap between high-caste and low-caste members. But in fact, the group members mainly belong to the backward and most backward castes, and they collectively form a category known as 'marginalized'. Investing in women's economic empowerment sets a direct path towards gender equality, poverty eradication, and inclusive economic growth. But they also remain disproportionately affected by poverty, discrimination, and exploitation.Are these women only seen as important end-users and beneficiaries to have a better life within the existing patriarchal system?